2022
DOI: 10.1186/s40104-022-00753-9
|View full text |Cite|
|
Sign up to set email alerts
|

Stimbiotic supplementation modulated intestinal inflammatory response and improved broilers performance in an experimentally-induced necrotic enteritis infection model

Abstract: Background Two experiments were conducted to establish an optimal NE challenge model and evaluate the efficacy of stimbiotic (STB) supplementation in necrotic enteritis (NE) challenged broilers. In Exp. 1, a total of 120 Arbor Acres (AA) broilers (45.0 ± 0.21 g) were randomly assigned to 6 treatments in a 3 × 2 factorial arrangement. Vaccine treatments included non-challenge (0), × 10 the recommended dose (× 10) or × 20 the recommended dose (× 20) by the manufacturer. Clostridium perfringens (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Reduced VH:CD and GC numbers indicate a deterioration in overall intestinal health, resulting in decreased nutrient absorption capacity and compromised mucosal barrier integrity ( McGuckin et al, 2011 ; Mora et al, 2020 ). Similar to previous studies ( Lee et al, 2022b ; Pham et al, 2022 ), the continuous turnover of crypt cells in response to inflammation caused by pathogens such as E. maxima and C. perfringens leads to increased crypt depth ( Paiva et al, 2014 ). Furthermore, various pathogens attempt to penetrate the mucin layer, and a decrease in the number of GCs can facilitate their infiltration into epithelial cells ( McGuckin et al, 2011 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Reduced VH:CD and GC numbers indicate a deterioration in overall intestinal health, resulting in decreased nutrient absorption capacity and compromised mucosal barrier integrity ( McGuckin et al, 2011 ; Mora et al, 2020 ). Similar to previous studies ( Lee et al, 2022b ; Pham et al, 2022 ), the continuous turnover of crypt cells in response to inflammation caused by pathogens such as E. maxima and C. perfringens leads to increased crypt depth ( Paiva et al, 2014 ). Furthermore, various pathogens attempt to penetrate the mucin layer, and a decrease in the number of GCs can facilitate their infiltration into epithelial cells ( McGuckin et al, 2011 ).…”
Section: Discussionsupporting
confidence: 78%
“…The current study observed an increase in water content as the E. maxima level increased, consistent with a previous NE-related study reporting an increase in diarrhea score with higher Eimeria spp. levels ( Lee et al, 2022b ). When diarrhea occurs, nutrients in the large intestine cannot be properly absorbed and are excreted from the body ( Bilgili et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was evident in reduced plasma APP concentrations (e.g., hemopexin and α−1-acid glycoprotein), a decreased number of intraepithelial lymphocytes, a thinner lamina propria, and reduced concentrations of inflammatory markers such as duodenal IL-6 on day 21 compared to the challenged control group. Similarly, in a study conducted by Lee et al [145], it was observed that broiler 1.…”
Section: The Role Of Dietary Exogenous Enzymes In Poultry and Pig Und...mentioning
confidence: 70%
“…Stimbiotics are expected to improve fiber fermentation in the lower gut without acting as a direct substrate for such fermentation [ 1 ]. Recent research has reported that stimbiotic supplementation enhanced animals’ growth rates and gut health by extracting extra energy from dietary fiber, increasing the utilization of the undigested dietary fiber by promoting fiber-degrading bacterium, breaking down the complex fiber structure into a lower degree of polymerization (DP) fiber, and eventually promoting the production of short-chain fatty acids (SCFAs) in the animal’s distal intestine [ 2 , 3 ]. It is well-known that SCFAs, as a main energy source of intestinal epithelial cells (IECs), play an important role in the improvement of the gut’s integrity and immune function.…”
Section: Introductionmentioning
confidence: 99%